Barriers to implementation of a pelvic examination among family doctors in primary care clinics. Issue 3 (3rd April 2018) - Saleh, Nassar; Abu-Gariba, Mousa; Yehoshua, Ilan; Peleg, Roni
ABSTRACT: Objective : although the pelvic examination of female patients should be an integral part of the physical examination in family medicine there are many barriers to the conduct of this intimate examination by family doctors. the objective: an assessment of the attitudes and barriers reported by family doctors on conducting a pelvic examination. Methods : An anonymous, self-administered questionnaire. Results : Two hundred thirty doctors participated in the study, of who 157 were males (68.9%). The mean age was 42.2 ± 9.6 years. 179 family doctors (77.8%) thought that the pelvic examination should be an important part of their work as a family doctor, 100 (43.9%) said that they had conducted a pelvic examination in the past, but the majority (85.2%) had not done a pelvic examination over the previous year. Senior doctors did more pelvic examinations than younger doctors (P = 0.007). Graduates of Israeli medical schools were more likely than those who graduated elsewhere to state that family doctors should do pelvic examinations (P = 0.032). Graduates of non-Israeli medical schools cited less experience (P = 0.002) and less motivation (P = 0.006) as reasons for not doing pelvic examinations. Conclusions : Although most family doctors believe that pelvic examinations are an important part of their work, only a small percentage actually do a pelvic examination. Among the reasons for not doing the examination are lack of knowledge, lack of experience, and work burden.